Information theory based detection against network behavior mimicking DDoS attacks - Shui Yu; Wanlei Zhou; Doss, R. (IEEE communications letters, 2008)
DDoS is a spy-on-spy game between attackers and detectors. Attackers are mimicking network traffic patterns to disable the detection algorithms which are based on these features. It is an open problem of discriminating the mimicking DDoS attacks from massive legitimate network accessing. We observed that the zombies use controlled function(s) to pump attack packages to the victim, therefore, the attack flows to the victim are always share some properties, e.g. packages distribution behaviors, which are not possessed by legitimate flows in a short time period. Based on this observation, once there appear suspicious flows to a server, we start to calculate the distance of the package distribution behavior among the suspicious flows. If the distance is less than a given threshold, then it is a DDoS attack, otherwise, it is a legitimate accessing. Our analysis and the preliminary experiments indicate that the proposed method- can discriminate mimicking flooding attacks from legitimate accessing efficiently and effectively.